Bukhta Abrekʺ po opisi Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago okeana 1917 g. / Sʺemka i chertilʺ Shtururmanʺ dalʹn. pl. P. Simonʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : Морское министерство, Главное гидрографическое управленіе, 1917)
Relief shown by form lines and spot heights. Depth shown by soundings.; Title translation: Abrek Bay, according to the survey of the Hydrographic Expedition of the Eastern Ocean in 1917.; "Masshtabʺ 1/8400 ili 100 s. vʺ 1 di︠u︡ĭmi︠e︡" = Scale 1/8400 or 100 fathoms in 1 inch Grayscale; 1:8,400